Identification and Functional Characterization of Two Putative Pheromone Receptors in the Potato Tuber Moth, Phthorimaea operculella - He, Xiaoli; Cai, Yajie; Zhu, Jinglei; Zhang, Mengdi; Zhang, Yadong; Ge, Yang; Zhu, Zengrong; Zhou, Wenwu; Wang, Guirong; Gao, Yulin (Frontiers in Physiology, 2021)
Pheromones are a kind of signal produced by an animal that evoke innate responses in conspecifics. In moth, pheromone components can be detected by specialized olfactory receptor neurons (OSNs) housed in long sensilla trichoids on the male antennae. The pheromone receptors (PRs) located in the dendrite membrane of OSNs are responsible for pheromone sensing in most Lepidopteran insects. The potato tuber moth Phthorimaea operculella is a destructive pest of Solanaceae crops. Although sex attractant is widely used in fields to monitor the population of P. operculella, no study has been reported on the mechanism the male moth of P. operculella uses to recognize sex pheromone components. In the present study, we cloned two pheromone receptor genes PopeOR1 and PopeOR3 in P. operculella. The transcripts of them were highly accumulated in the antennae of male adults. Functional analysis using the heterologous expression system of Xenopus oocyte demonstrated that these two PR proteins both responded to (E, Z)-4,7–13: OAc and (E, Z, Z)-4,7,10–13: OAc, the key sex pheromone components of P. operculella, whilst they responded differentially to these two ligands. Our findings for the first time characterized the function of pheromone receptors in gelechiid moth and could promote the olfactory based pest management of P. operculella in the field.